2013
DOI: 10.4049/jimmunol.1202662
|View full text |Cite
|
Sign up to set email alerts
|

GILZ Overexpression Inhibits Endothelial Cell Adhesive Function through Regulation of NF-κB and MAPK Activity

Abstract: Glucocorticoid-induced leucine zipper (GILZ) is an anti-inflammatory protein first identified in T lymphocytes. We recently observed that GILZ is highly expressed in synovial endothelial cells in rheumatoid arthritis. However, the function of GILZ in endothelial cells is unknown. To investigate the actions of GILZ in this cell type, we induced GILZ expression in HUVECs via transient transfection. GILZ overexpression significantly reduced the capacity of TNF-stimulated HUVECs to support leukocyte rolling, adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 47 publications
7
67
0
Order By: Relevance
“…GILZ is known to homo-or heterodimerize with partner proteins, such as, NF-kB, CCAAT/enhancer binding protein, and Ras, but is unable to bind to DNA to regulate the transcription of target genes (7,13,28,57,58). Our findings on the regulation of Anxa1 expression by GILZ indicate that the control is at the transcription level, which implies the presence of a binding cotranscription factor on the Anxa1 promoter.…”
Section: Discussionmentioning
confidence: 64%
“…GILZ is known to homo-or heterodimerize with partner proteins, such as, NF-kB, CCAAT/enhancer binding protein, and Ras, but is unable to bind to DNA to regulate the transcription of target genes (7,13,28,57,58). Our findings on the regulation of Anxa1 expression by GILZ indicate that the control is at the transcription level, which implies the presence of a binding cotranscription factor on the Anxa1 promoter.…”
Section: Discussionmentioning
confidence: 64%
“…For instance, TAT-GILZ administration promoted a protective effect in a model of inflammatory bowel disease (9) and spinal cord injury (12). Moreover, recent studies showed that GILZ overexpression inhibits endothelial cell adhesion function (42) and protects against endotoxemia (43) and arthritis (13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its ability to bind to NF-kB and AP-1, GILZ has also been reported to interfere with MAPK signaling (3,7,8,23,30,31). MAPKs modulate various physiological cell processes, such as proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…GILZ has been suggested to modulate MAPK signaling in various cell types (3,7,8,23,30,31). Therefore, we examined LPS-induced p38, JNK, and ERK activation in WT and GILZ KO cells.…”
Section: Sensitization Of Gilz Ko Macrophages Toward Lps Is Facilitatmentioning
confidence: 99%
See 1 more Smart Citation